Vulnerability and Bargaining Power in EU-Russia Gas Relations - Edward Hunter Christie; Pavel K. Bev; Volodymyr Golovko (FIW - Research Centre International Economics, 2011)
This report contains three separate papers, each addressing selected issues concerning natural gas policy and security of gas supply in Europe. The over-arching themes are vulnerability (to supply disruptions, to supplier pricing power) and fragmentation; and measures designed to overcome them, namely interconnection and consolidation of bargaining power. The first paper contains a review of some of the economic effects of, and subsequent policy reactions to, the January 2009 cut of Russian gas supplies through the Ukraine Corridor, with a particular focus on Bulgaria and on EU policy. The second paper provides an analysis of the current state of gas relations between Ukraine and the Russian Federation, with a focus on the Ukrainian perspective and on recent political developments in that country. The third paper provides an analysis of the case for consolidating buyer power in line with the concept of an EU Gas Purchasing Agency.
Keywords: C78; L11; Q34; Q48; 330; Natural gas; security of supply; supply disruption; interconnector; Russia; Ukraine; Bulgaria; European Union; energy policy; fragmentation; bargaining power; countervailing power; gas purchasing agency